Pengaruh Influencer Marketing, Perceived Quality, dan Bundling Product terhadap Keputusan Pembelian Produk Daviena Skincare di Tiktokshop (Studi pada pengguna Tiktok) - Adilah Nur Fadilah; Rama Chandra Jaya (Komunitas Dosen Indonesia, 2024)
The ultimate goal of this research is to assess the level of impact of Influencer Marketing, Perceived Quality and Bundling Product on Purchasing Decisions. The approach used is quantitative using a test sample of 100 sources. The results of this observation state that Influencer Marketing causes purchasing decisions and sig score 0.000 < 0.05 then t score of 8.559 > t distribution table 1.985. The Perceived Quality causes purchasing decisions and sig score 0.031 < 0.05 then t score of 2.193 > t distribution table 1.985. The Bundling Product causes purchasing decisions and sig score of 0.035 < 0.05 then t score of 2.134 > t distribution table 1.985. And simultaneously F count 103.231 > F distribution table 2.47 along with relevant scales of 0.000 < 0.05. This condition proves that the Influencer Marketing, Perceived Quality, and Product Bundling causes purchasing decisions. The squared correlation coefficient score in this research is 0.763 or 76.3% and 23.7% are other components not analyzed in this research.